Autoimmune diseases and cancers overlapping with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD): A systematic review. Issue 4 (October 2022) - Molazadeh, Negar; Bose, Gauruv; Lotan, Itay; Levy, Michael
Background: Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) has various similarities with AQP4-IgG-seropositive Neuromyelitis Optica Spectrum Disorder (AQP4-IgG + NMOSD) in terms of clinical presentations, magnetic resonance imaging (MRI) findings, and response to treatment. But unlike AQP4-IgG + NMOSD, which is known to coexist with various autoimmune diseases and cancers, an association of MOGAD with these conditions is less clear. Methods: We conducted a systematic search in PubMed, Scopus, Web of Science, and Embase based on the preferred reporting items for systematic reviews and meta-analysis (PRISMA). Duplicates were removed using Mendeley 1.19.8 (USA production) and the citations were uploaded into Covidence systematic review platform for screening. Results: The most common autoimmune disease overlapping with MOGAD was anti-N-Methyl-D-Aspartate receptor encephalitis (anti-NMDAR-EN), followed by autoimmune thyroid disorders, and the most common autoantibody was antinuclear antibody (ANA), followed by AQP4-IgG (double-positive MOG-IgG and AQP4-IgG). A few sporadic cases of cancers and MOG-IgG-associated paraneoplastic encephalomyelitis were found. Conclusion: Unlike AQP4-IgG + NMOSD, MOGAD lacks clustering of autoimmune diseases and autoantibodies associated with systemic and organ-specific autoimmunity. Other than anti-NMDAR-EN and perhaps AQP4-IgG + NMOSD, the evidence thus far does not support the need for routine screening of overlapping autoimmunity and neoplasms in patients with MOGAD.